1997
DOI: 10.1103/physrevd.55.7059
|View full text |Cite
|
Sign up to set email alerts
|

Bql+lγdecays in light cone QCD

Abstract: The radiative dileptonic decays B s (B d )→l ϩ l Ϫ ␥ (lϭe,) are investigated within the standard model. The transition form factors are calculated in the framework of the light cone QCD sum rule method and it is found that the branching ratios areA comparison of our results with the constituent quark model predictions on the branching ratios is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
128
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(136 citation statements)
references
References 0 publications
4
128
4
Order By: Relevance
“…Indeed in [5] it was shown that the B(B → e + e − γ) ≃ 2.35 × 10 −9 . For B → ℓ + ℓ − γ (ℓ = e, µ), the contributions of the diagrams, where photon is radiated from any charged internal line, can safely be neglected, as they are strongly suppressed by a factor m 2 b /m 2 W in the Wilson coefficients (see [5]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed in [5] it was shown that the B(B → e + e − γ) ≃ 2.35 × 10 −9 . For B → ℓ + ℓ − γ (ℓ = e, µ), the contributions of the diagrams, where photon is radiated from any charged internal line, can safely be neglected, as they are strongly suppressed by a factor m 2 b /m 2 W in the Wilson coefficients (see [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed in [5] it was shown that the B(B → e + e − γ) ≃ 2.35 × 10 −9 . For B → ℓ + ℓ − γ (ℓ = e, µ), the contributions of the diagrams, where photon is radiated from any charged internal line, can safely be neglected, as they are strongly suppressed by a factor m 2 b /m 2 W in the Wilson coefficients (see [5]). Moreover, it follows from helicity arguments that, the contributions of the diagrams where a photon is emitted from the final charged lepton lines, must be proportional to the lepton mass m ℓ (ℓ = e, µ), and hence they are negligible as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are already many methods calculating the heavy-to-light transition form factors in the literature such as simple quark model [2], the light cone quark models (LCQM) [4,5,6,7] 1 , the light cone sum rules (LCSR) [8,9,10], the perturbative QCD (PQCD) approach based on k T factorization [11] etc.…”
Section: Introductionmentioning
confidence: 99%
“…(9) and (10), first of all, we need the expressions for the form factors. For the values of the form factors, we have used the results of [23] (see also [24] and [25]), where the radiative corrections to the leading twist contribution and SU(3) breaking effects are also taken into account. It is shown in [23] that the q 2 dependence of the form factors can be represented in terms of three parameters as…”
Section: Numerical Analysismentioning
confidence: 99%